The natural ocean acidification and fertilization event caused by the submarine eruption of El Hierro - Santana-Casiano, J. M.; González-Dávila, M.; Fraile Nuez, Eugenio; Armas, Demetrio de; González, A. G.; Domínguez-Yanes, J.F.; Escánez, J. (Scientific Reports, 2017)
The shallow submarine eruption which took place in October 10th 2011, 1.8 km south of the island of El Hierro (Canary Islands) allowed the study of the abrupt changes in the physical-chemical properties of seawater caused by volcanic discharges. In order to monitor the evolution of these changes, seven oceanographic surveys were carried out over six months (November 2011-April 2012) from the beginning of the eruptive stage to the post-eruptive phase.